Особливості бухгалтерського обліку в умовах інформаційної економіки - Ілляшенко, Катерина Володимирівна; Илляшенко, Екатерина Владимировна; Illiashenko, Kateryna (My University, 2012)
RU: В статье рассмотрены основные этапы информатизации экономики, проанализировано ее влияние на методологию бухгалтерского учета, предложены направления усовершенствования бухгалтерского учета предприятий в условиях информационной экономики. EN: In clause the basic stages of information of economy are considered, its influence on methodology of accounting is analysed, the directions of improvement of accounting of the enterprises in conditions of information economy are offered.
Keywords: информация; экономика; бухгалтерский учет; the information; economy; accounting